ETNOGRAFI KRITIS DALAM PENELITIAN SEJARAH: SEBUAH TINJAUAN KONSEPTUAL - Ody Aulia Ramadhan, Puput Indah Giri, Leli Yulifar (FKIP UMN ALWASHLIYAH, 2026)
Historical studies have often focused on major events and official sources that tend to represent dominant groups. As a result, the experiences of marginalized groups receive less attention. Therefore, an approach that can present more diverse and contextual perspectives is needed. This study aims to examine critical ethnography as an approach in historical research through a conceptual review. This research employs a qualitative method with a library research approach by analyzing various relevant literature on critical ethnography and historical studies. The findings show that critical ethnography plays an important role in expanding historical sources, uncovering power relations, and bringing forward the social experiences of communities that have often been overlooked. In addition, this approach encourages critical awareness of social injustices in the past and their impact on the present. However, critical ethnography also has limitations, such as a high level of subjectivity, complex research processes, and difficulties in generalization. Nevertheless, this approach remains relevant in enriching historical studies, particularly in providing more reflective, inclusive, and socially grounded understandings.